2016
DOI: 10.1201/b15366
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Techniques in Participatory Forest Management

Abstract: This book contains information obtained from authentic and highly regarded sources. Reasonable efforts have been made to publish reliable data and information, but the author and publisher cannot assume responsibility for the validity of all materials or the consequences of their use. The authors and publishers have attempted to trace the copyright holders of all material reproduced in this publication and apologize to copyright holders if permission to publish in this form has not been obtained. If any copyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 561 publications
(948 reference statements)
0
6
0
Order By: Relevance
“…In recent studies, the scope of participatory management has been extended to projects involving multiple stakeholders. For this reason, a large number of studies applying participatory management can be found in the field of environmental sciences, where the natural and the human system is linked and different groups expand on mutually agreed solutions in a bid to protect the environment [27,28]. Nutrition and health sciences is another field where participatory management is applied, as researchers need to understand patients' habits and attitudes in order to identify and offer adequate solutions [29].…”
Section: Overview Of the Participatory Conceptmentioning
confidence: 99%
“…In recent studies, the scope of participatory management has been extended to projects involving multiple stakeholders. For this reason, a large number of studies applying participatory management can be found in the field of environmental sciences, where the natural and the human system is linked and different groups expand on mutually agreed solutions in a bid to protect the environment [27,28]. Nutrition and health sciences is another field where participatory management is applied, as researchers need to understand patients' habits and attitudes in order to identify and offer adequate solutions [29].…”
Section: Overview Of the Participatory Conceptmentioning
confidence: 99%
“…In this study, we followed the second approach. Several remotely sensed vegetation indices have been used as ecophysiological indicators (Manzanera et al 2013). These indices are associated with plant water stress (Suárez et al 2008) or radiation use efficiency (Garbulsky et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Public participation, as a key element of environmental decision-making, is a very recent idea and policy trend in the West. Participatory approaches to forest management were introduced in the 1970s, before which forestry management decisions tended to be top-down (Martinez-Falero et al, 2013). Major international initiatives and laws have only been adopted in the last couple of decades, for example the 1992 UN Rio Declaration, Agenda 21, the 1998 UN Aarhus Convention or the European Water Framework Directive 2000.…”
Section: Lessons From Pfm In the Westmentioning
confidence: 99%
“…Despite the European Union being at the forefront of promoting and adopting participatory natural resource management practices, implementation has been rather variable across countries, and participation is often limited to information and consultation of stakeholders, without having a significant impact on policy design; the shift from centralized resource management towards more collaboration has been marginal, and power remains largely concentrated (e.g. Benson et al, 2012;van der Heijden and ten Heuvelhof, 2012;Martinez-Falero et al, 2013). Environmental policies outside Europe also remain highly path-dependent, and the history of US environmental policy is 'a story of perennial conflicts among organized advocates of various specific commercial or appreciative uses of natural assets' (Kamieniecki and Kraft, 2012: 41).…”
Section: Lessons From Pfm In the Westmentioning
confidence: 99%
See 1 more Smart Citation